Content management strategy for the social network Facebook, of Cuban scientific journals indexed in SciELO - Viera Savigne, Alina (2025)
Purpose. Scientific journals create profiles in social networks as a way to improve their visibility. The objective of this research is to analyze the content management strategy in the social network Facebook, for Cuban scientific journals indexed in SciELO, which contributes to improve the public communication of science. Methodology. The research of descriptive type, with qualitative and quantitative character, used the survey and observation to identify the behavior of the dimensions: value of the content, visual structure and strategy through the indicators established for each dimension, in turn it was determined by means of an ordinal scale of three levels, the state in which the content management variable is. Results and conclusions. The results show that Cuban scientific journals do not take advantage of the facilities offered by the social network Facebook for science communication; in turn, the dimensions and the variable only reach Level I Little achieved, which is the farthest from the desired state. Based on the deficiencies and strengths found in the study, a strategy is proposed to increase the visibility, positioning and reach of the journals. Original contributions. The research serves as a contribution to propose guidelines that favor the development of a content management strategy, oriented to the dissemination of science in the field.